Adaptabilidade e estabilidade de linhagens de arroz de terras altas por meio da lógica fuzzy - Maciel, Douglas de Oliveira (2022)
The selection of lines for characters of agronomic interest is done with evaluations in different environments. As the environments are diversified and several lines are evaluated, it is expected that the interaction between genotypes by environments will occur, and that it will play an important role in the manifestation of the phenotype. Adaptability and stability studies have been used in breeding programs to help the selection process where the interaction of genotypes by environments has been reported. The evaluation is based on parameters provided by methodologies and requires the breeder's experience, making it difficult as the number of evaluated genotypes increases. Fuzzy logic stands out for allowing the automation of decision making, and also classifying how much a genotype belongs to each set. The objective of this work was to evaluate the genotypes in terms of adaptability and stability through fuzzy logic, using data on agronomic characters of upland rice from the breeding program of UFG and partners. Eight lines from the UFG breeding program, ten from UFLA and two commercial cultivars were evaluated for grain yield, plant height and number of days to flowering, in VCU trials at six locations in the state of Goiás in four agricultural years, in the 2017/18 to 2020/21 harvests. The trials varied between locations over the years, totaling thirteen environments for grain yield and plant height, and eight environments for number of days to flowering. The design was complete randomized blocks, with three replications, and plots of four lines of 4 meters, spaced by 0.45 meters. The useful area considered was 3 meters from the central lines. The adaptability and stability analyzes considered a fuzzy controller based on the Eberhart and Russell (1966) method, and a hybrid controller, based on the Lin and Binss (1988) methods, modified by Carneiro (1998) and associated with Eberhart and Russell (1966). Both controllers classified the lines into four sets in terms of performance relative to adaptability and stability (general, poorly adapted, favorable environments, unfavorable environments). The CSD 08004 line showed broad adaptability and stability for plant height and grain yeld, in addition to a pertinence value close to classification as adaptability and general stability for the number of days to flowering. Thus, the CSD 08004 line can be recommended for cultivation in the region of the State of Goiás.